(untitled) (Computer-Assisted Language Learning Electronic Journal, 2024)
This article reviews second language (L2) motivation studies in the classroom and computer-assisted language learning (CALL) contexts with a focus on theoretical trends. Given the differences in these two contexts, it was highly critical to trace the theoretical trajectory and predict the future direction of L2 motivation theory with respect to reported theoretical inconsistencies and calls for theoretical reevaluations. The rigorous review of 158 major studies in two educational fields revealed that despite the popularity of the L2 Motivational Self System in classroom context studies, it is not equally welcomed and adopted in the CALL context. Accordingly, a critical review of the L2 Motivational Self System provided an opportunity to highlight decade-long overlooked reports of inconsistencies and calls to revisit the current L2 motivation theories. Outlining the main theoretical trends and predicting the future direction of L2 motivation studies, the findings have theoretical and pedagogical implications for the broader field of second language acquisition.